European constitutionalism beyond the state - Weiler, Joseph, 1951-; Wind, Marlene, 1963- (Cambridge University Press, 2003)
Leading scholars of European constitutionalism highlight different facets of the new constitutional discussion. This book delineates new ways of thinking about the future of Europe. This book will appeal to anyone interested in the timely subject of constitutionalism including students and practitioners of law, politics and philosophy.
Keywords: Constitutional law -- European Union countries.; European Union countries -- Politics and government.; Droit constitutionnel -- Pays de l'Union européenne.; Union européenne.; Pays de l'Union européenne -- Politique et gouvernement.; LAW -- International.; Constitutional law; Politics and government; European Union countries; Aufsatzsammlung; Verfassung; Democratisering.; Constitutionalisme.; Europese Unie.; Droit constitutionnel (droit européen); Constitutionnalisme -- Pays de l'Union européenne.; Europäische Union.; Electronic books.